Locker hero - Russell, Rachel Renée; Russell, Erin; Russell, Nikki (New York Aladdin, 2016)
Questioning his resolve to attend public school after being homeschooled when he is targeted by a bully, Max aspires to become like his favorite comic book heroes and finds an unexpected opportunity to be the hero his middle school needs.
Ages 9-13.
Keywords: Literature; Literature; Literature; Literature; Literature; Literature; Literature; Literature; Literature